The developmental trajectory of time perspective through lifespan: childhood, adolescence, old age, and its relationship with age - lakmache, nourimane (Journal of Social Sciences and Humanities, 2025)
In psychology, time is often referred to as “the tacit dimension”, because unlike other types of perception, it is not directly available to any sensory organ but can only be apprehended through the change and the dynamic flow of environmental events, and yet despite its ephemeral nature, time is a dimension that has a significant impact upon a wide variety of psychological behavior, time is also viewed as “psychological time”, it depends on how we think about it. And the way we think about time is related to our frame of reference. Research throughout the years have focused on exploring the relationships between time perspective and many aspects of human functioning and human behavior. However, relatively less attention has been given to how time perspective changes throughout the lifespan and its relationship with age. To move the field forward in these areas, a discussion of a developmental trajectory of time perspective through lifespan from childhood to older age is provided, in addition to an overview of the history and concept of time perspective, research on its developmental trajectory and its association with age.